DIALEKTIKA PENDIDIK DAN PERUBAHAN KURIKULUM DI MASA PANDEMI - Wikan Ningsih, Agustin Ayu; Nafis, Muhammad Muntahibun (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
The educational curriculum in Indonesia is very dynamic. Curriculum changes occur because it adapts to the times and society. This flexibility follows a growing era and increasingly sophisticated technology or is related to problems in a country. This paper examines the influence of the Covid-19 Pandemic which has spread to Indonesia, causing the government to create an emergency curriculum for the smooth running of the learning system. Learning is usually done face-to-face in a place, but now takes place face-to-face with a distance and relies on the existence of communication technology. This study uses a qualitative-descriptive-analytical approach with data sources from various educational institutions both based on Islam and the general public. Data obtained from educators by in-depth interviews. The results of the study explain that the impact of this learning system change on the learning process, understanding of a lesson, and the character of students. Changes in the curriculum during the pandemic were not completely, but rather in the design of learning by educators that included methods, media, to evaluation and the time used. Synergy and good communication are needed between the institution, educators, students and parents so that there are no problems that hinder learning.